2017
DOI: 10.1245/s10434-016-5748-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Oncologic Significance of Perineural Invasion in Sporadic Colorectal Cancer

Abstract: PNI positivity is an independent predictor of aggressive behavior and unfavorable prognosis in CRC. Further evaluation is needed to confirm the impact of PNI status on survival in stage IIA CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 28 publications
5
35
5
1
Order By: Relevance
“…These included prostate, seminal vesicle, bladder, posterior wall of vagina and uterus. Perineural invasion is an independent predictor of survival independent of TNM staging, which may require adjuvant therapy even in stage II tumours . Only small numbers of aggressive histological types of rectal cancers were identified, including two signet cell cancers both of which had positive CRM.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…These included prostate, seminal vesicle, bladder, posterior wall of vagina and uterus. Perineural invasion is an independent predictor of survival independent of TNM staging, which may require adjuvant therapy even in stage II tumours . Only small numbers of aggressive histological types of rectal cancers were identified, including two signet cell cancers both of which had positive CRM.…”
Section: Discussionsupporting
confidence: 76%
“…Patients undergoing APR are more likely to have locally advanced and distal tumours increasing the complexity of resection . Although extra‐levator APR in the prone jack‐knife position has been demonstrated to have improved oncological outcomes and a lower CRM positivity rate, uptake of this technique has been limited to two or three surgeons in our region, and we were unable to determine APR technique in our data‐set. T4 tumours were very strongly associated with CRM positivity and represented 66.7% of those with positive CRM, with 22 (48%) of these requiring an en‐bloc multi‐visceral resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PNI was significantly associated with recurrence and poor survival outcome in pancreatic cancer, prostate cancer and colorectal cancer 11–14. Furthermore, there have been several studies evaluating the prognostic significance of PNI for GC patients, but the results were conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…To address this, efforts have been made to identify factors beyond the standard Tumor, Node, and Metastasis classification to stratify risks of recurrence and mortality. As a result, pathological and molecular features including poorly differentiated cancers, lymphovascular invasion, perineural invasion, and microsatellite instability have been validated as risk factors …”
Section: Introductionmentioning
confidence: 99%